An exploration of school-community links in enabling environmental learning through food growing : a cross-cultural study - Köhly, Nicolette (Rhodes University, Faculty of Education, Department of Education, 2010)
Agricultural and educational researchers recognize the critical value of an integrated, multidisciplinary approach to education in building a food-secure world, reducing poverty, and conserving and enhancing natural resources. However, schools generally contribute little to communities in the context of food growing and environmental learning. The main objective of this qualitative research was to explore the role of school-community relationships in enabling environmental learning in the context of food growing activities. Findings suggest that the role of school-community links in enhancing environmental learning is more likely where community members are actively involved in school programs that have an emphasis on an experiential learning approach. However, this depends to a large extent on the availability of parents or concerned community members and their willingness to engage in voluntary school-based activities. Factors that could potentially strengthen the role of school-community links in supporting environmental learning include: allowing space for informal learning, mediating learning in civil society settings, ongoing facilitation by a committed coordinator, community buy-in and accountability, and addressing public interests through tangible benefits. A major challenge is to find an appropriate balance between social justice and practical food security concerns, while remaining true to ecological considerations.
Keywords: Environmental education -- Africa, Southern -- Case studies; Environmental education -- New York (State) -- Case studies; Sustainable agriculture -- Africa, Southern -- Case studies; Sustainable agriculture -- New York (State) -- Case studies; Environmental education -- Study and teaching -- Africa, Southern -- Case studies; Environmental education -- Study and teaching -- New York (State) -- Case studies; Conservation of natural resources -- Study and teaching -- Africa, Southern -- Case studies; Conservation of natural resources -- Study and teaching -- New York (State) -- Case studies; Active learning -- Africa, Southern -- Case studies; Active learning -- New York (State) -- Case studies; Community education -- Africa, Southern -- Case studies; Community education -- New York (State) -- Case studies